Comparative Statistical Analysis of Gender Equality on the Labour Markets of Romania and EU28 - PAŞNICU, Daniela (Annals of Spiru Haret University. Economic Series, 2015)
To achieve the employment target set in the Europe 2020 Strategy is necessary that women's potential and talent to be used optimally. Increasing employment for both men and women is the main way to achieve autonomy, financial independence and poverty reduction. This paper presents a comparative statistical analysis of gender equality on the labour markets of Romania and EU28 based on official statistics records and specific key labour market indicators. The aim was to highlight the gender gap on activity rates, employment rates by age, work time and unemployment rate, including long-term unemployment. The analyses undertaken shows that in the last ten years activity and employment rates of women in Romania had a slightly decreasing trend, while at the EU28 level had an upward trend, which led to the widening gap than the average EU28. The gender gap for the same indicators rose in the period under review, in the case of Romania, while at the EU28 level decreased.